Modelling Biodiesel Production of Banking Scheme With Spline Regression (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
The portion of renewable energy, one of which is biodiesel production in Indonesia, still relatively low due several obstacles, such as the banking financing scheme. Therefore, this research was carried out by involving banking variables, including the banks, third parties fund and Gross Domestic Regional Product of each province to find the best model that affected the rate of biodiesel production in Indonesia. The Spline Regression method was employed here. Modelling the rate of biodiesel production was done by using the knots point method with the smallest GCV Value. Based on the findings, all variables had an influence with a coefficient of determination of 50%, meaning that the model formed was feasible to use in the modelling data patterns. Among these 3 variables, the variable banks had the best influence in determinang tha rate of biodoesel production in each province in Indonesia. In conclusion, the financing scheme from the banking side is an important thing to do considering that the more the number banks in a province, the greater the development potenstial of biodiesel production from each of these provinces.